A novel approach to bedside pretransfusion identity check of blood and its components: the Sandesh Positive-Negative protocol - Udupi, Sandesh (Korean J Anesthesiol, 2020)
BACKGROUND: Blood component mistransfusion is generally due to preventable clerical errors, specifically pretransfusion misidentification of patient/blood unit at bedside. Hence, electronic devices such as barcode scanners are recommended as the standard instrument used to check the patient’s identity. However, several healthcare facilities in underdeveloped countries cannot afford this instrument; hence, they usually perform subjective visual assessment to check the patient’s identity. This type of assessment is prone to clinical errors, which precipitates significant level of anxiety in the healthcare personnel transfusing the blood unit. Hence, a novel objective method in performing pretransfusion identity check, the ‘Sandesh Positive-Negative (SPON) protocol,’ was developed. METHODS: A nonrandomized study on bedside pretransfusion identity check was conducted, and 75 health care personnel performed transfusion. The intervention was performed by matching a custom-made negative label with blood component with the positive label of the same patient available at bedside who was about to receive transfusion. RESULTS: In total, 85.3% of the subjects were anxious while performing pretransfusion identity check based on the existing standard practice. After the implementation of the SPON protocol, only 38.7% experienced either mild, moderate or severe anxiety. The overall level of satisfaction also increased from 8.0% to 38.7% and none were dissatisfied. Although only 9.3% were dissatisfied about the existing practice, approximately 70.7% felt the need for a better/additional protocol. Clerical error was not observed. CONCLUSIONS: The SPON protocol is a cost-effective objective method that reduces anxiety and increases satisfaction levels when performing final bedside identity check of blood components.